Functional differentiation of law in pandemic times - Germano Schwartz; Renata Almeida da Costa (Oñati Socio-Legal Series)
Between 2020 and 2023, a period of time assailed by the COVID-19 pandemic, society – as a worldwide social system –experienced a novel kind of communication. The tendency for this communication to exponentially expand is due to the global numbers of people dead, dying or infected. Pandemic communication has arisen in the present to perpetuate itself in all ambiences for every social system around the globe. The health system, in turn, basing itself on the health/disease code, has reacted according to its own logic in the coordination of the actions of doctors. However, the true/false nature of communication arising from questions related to COVID-19 has taken a long time to be tested by the science system. Vaccines and possible treatments for the disease have created issues for political, economic, moral, religious and media matters. The continually expanding trend in pandemic communication has proven that it can hinder the functional differentiation of social systems. Legal communication has not been able to avoid all of the controversy. In the specific case of Law, the problem entails both the judicialization of health and the reverse (where Health becomes Law). Based on the Social Systems Theory Applied to Law, the paper argues that the maintenance of the functional differentiation of the Law system becomes necessary so as for Health not to become Law (and vice versa).